VALIDASI HOTSPOT MODIS DI WILAYAH SUMATERA DAN KALIMANTAN BERDASARKAN DATA PENGINDERAAN JAUH SPOT-4 TAHUN 2012 - Zubeidah, Any; Vetrita, Yenni; Khomarudin, M. Rokhis (Institut Teknologi Sepuluh Nopember, 2014)
Forest/land fire indicator can be indicated by fire smoke and hotspot. Currently hotspot information has been widely used but its accuracy remains disputed. Therefore validated hotspot is needed as a proper effort of disaster management. This study aims to examine the accuracy of the hotspot as an indicator of forest fire/land from two data sources, namely IndoFire Map Service (IndoFire) and Fire Information for Resource Management System (FIRMS-NASA). Validation is done by comparing the data hotspot with a higher resolution image, i.e. SPOT-4 for 2012. The results show that the value of hotspot FIRMS acquired by 42% with error of 20% Commissioned 38% Omission error. Furthermore, analysis showed slightly better accuracy by 66% with 19% commission error and 18% error omission for FIRMS data compared to IndoFire ID using 46% with 19% commission error and 20% omission error. The value of confidence level of hotspot is very much affected by smoke and haze that is detected by the method of MODIS algorithm which is very sensitive to the condition of the environment. The results indicate that the accuracy of hotspot data can be considered for use in the field as a warning for forest fire, but should be considered for the data with a confidence level greater than 80%.